Asset Recovery as an Effort to Restore State Losses Resulting from Corruption Cases - Khumaeroh, Irda Nur; Bagaskoro, M. Rizal (Journal of Law, Politic and Humanities, 2025)
Eradicating corruption solely by prosecuting and imposing imprisonment on perpetrators does not fully resolve the problem if the assets obtained from corrupt practices cannot be recovered by the state for development purposes. Therefore, the recovery of assets resulting from corruption becomes a crucial aspect of combating corruption. This study uses a normative legal research method, which emphasizes document studies or literature research. The substance of the asset recovery legal system through criminal law consists of four stages: asset tracing, asset freezing or confiscation, asset seizure, and the return and transfer of assets to the victim state. Efforts to recover state losses caused by corruption cases through asset recovery include seizing and tracing the assets of defendants or convicts, ensuring that convicts pay compensation, encouraging public support for anti-corruption initiatives, improving facilities and infrastructure for corruption eradication, and clearly regulating—based on applicable laws—the authority of KPK prosecutors and public prosecutors appointed and dismissed by the Corruption Eradication Commission.